Simulation research on trajectory tracking control system of manipulator based on fuzzy PID control. (19th January 2023) - Ma, Ruyi; Li, Zeshen; Jiang, Du; Yun, Juntong; Liu, Ying; Liu, Yibo; Bai, Dongxu; Li, Gongfa
In view of the influence of external environment interference, parameter changing and random noise in the process of manipulator trajectory tracking, as well as the problems of fuzzy PID control, such as fuzzy rules are not easy to set, quantisation interval and parameters are affected by subjective consciousness, which leads to the problem of insufficient performance of manipulator system. In this paper, firstly, in the MATLAB simulation environment, based on the D-H parameter model, the linkage model of the four degree of freedom manipulator is established, and the homogeneous transformation matrix of the manipulator is calculated. Then, through the application of fuzzy PID control in the Simulink toolbox, the optimal parameters of the controller are found by using the proportion factor self-adjusting strategy, and the corresponding trajectory tracking and forward inverse kinematics simulation are studied. The trajectory tracking curve of the manipulator is obtained. The research method and experimental results in the paper are of great significance for the simulation of articulated manipulator.